Multi-spectroscopic and elemental characterization of southern Australian asphaltites - Scarlett, Alan; Holman, Alex; Georgiev, S.V.; Stein, H.J.; Summons, R.E.; Grice, Kliti (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Strandings of various types of bitumen along the coast of southern Australia are long known. Among these, brittle, angular lumps termed ‘asphaltites’ are possibly sourced from Cretaceous source rocks linked to an oceanic anoxic event (OAE), but the exact source remains unclear. The unusual chemical composition of these asphaltites and their survival during transport and shoreline stranding suggest that they formed by nearby submarine seepage of asphaltene-rich crude oils. Here, we provide a detailed organic and inorganic geochemical characterization of asphaltites to constrain their origin and age. High-pressure hydropyrolysis (HyPy) of asphaltene fractions from ten asphaltites released similar assemblages of macromolecularly bound compounds, suggesting a common source for all asphaltites. Comprehensive gas chromatography–time-of-flight mass spectrometry (GC×GC-TOFMS) was used to compare these asphaltene-derived compounds with the maltene fractions, while compound specific isotope analysis (CSIA) was used to compare δ13C and δ2H of n-alkanes and isoprenoids. A large offset between the δ2H of the n-alkanes and isoprenoids suggests oil generation and expulsion at low thermal maturity. The mean concentrations of isorenieratane and chlorobactane, carotenoid derivatives indicative of photic zone euxinia (PZE), in the asphaltites were 8.8 ± 0.8 SEM µg g−1 and 1.4 ± 0.1 SEM µg g−1, respectively. A mean Aryl Isoprenoid Ratio of 0.75 (SD = 0.17) is accompanied by Pr/Ph of ∼1.2. These features strongly support persistent PZE conditions at the level expected for an OAE. Trace metal contents of the asphaltites, including low selenium and high vanadium concentrations, also support anoxic conditions. Rhenium-osmium (Re-Os) analyses constrain the age of asphaltite generation to 103 ± 22 Ma, with a relatively low initial 187Os/188Os ratio of 0.44 ± 0.18. Integrating local geologic knowledge with organic and inorganic geochemistry and Re-Os isotopic results, we identify a Cretaceous unit associated with OAE1a (∼125 Ma) as the most likely source of the asphaltites. Alternative scenarios involving source rocks deposited during OAE1b (∼112 Ma) are possible, but require rapid burial of organic-rich sediments to reach required maturation levels in a shorter time.